Cyclic performance of composite shear walls with boundary elements. (October 2020) - Haghi, Nakisa; Epackachi, Siamak; Taghi Kazemi, Mohammad
Abstract: In the past three decades, several experiments were conducted to investigate the seismic behavior of composite plate shear walls (C-PSW) because of their advantages to conventional reinforced concrete (RC) and steel plate shear walls (SPSW). Numerical studies, however, are limited due to the complexities for the finite element modeling of the steel and concrete material behaviors and their composite action. Herein, the cyclic behavior of various C-PSW with and without boundary elements (BE) is investigated numerically. The effects of design parameters such as aspect ratio, axial load ratio, and the length of the BE on the response of C-PSW are investigated. The advanced finite element software LS-DYNA is utilized to develop the cyclic model of C-PSW. The LS-DYNA model is validated using the available experimental data in the literature. Numerical analyses indicate that the‌‌ BE has a significant impact on the stiffness, strength, and energy absorption of C-PSW especially in high aspect ratio walls. A simplified method is proposed to estimate the peak shear strength of C-PSW with BE using the results of the numerical and experimental study.